IMPLEMENTASI PROGRAM PENANGGULANGAN KEMISKINAN (STUDI KASUS DI KECAMATAN LATAMBAGA KABUPATEN KOLAKA PROVINSI SULAWESI TENGGARA) - Sabaruddin, Abdul; Maulid, Maulid (Universitas Islam Negeri Raden Fatah Palembang, 2017)
This paper would like to explain the implementation of poverty reduction program in Latambaga Kolaka District. A qualitative approach is used to look at social phenomena related to human behavior and work processes. Observational case study, directed to specific groups and networks of actors involved in poverty reduction policy formulation In accordance with the theme of policy studies. The information data obtained in analyzed by using interactive model. These poverty alleviation programs do not seem to have changed lives for the target community. Kolaka Regency Government encountered obstacles with limited limitations both organizational, management and finance. Even the main obstacle is the behavior of the beneficiary community. A finding in the field, another factor that has not been effective in poverty reduction programs is the unavailability of valid poverty data.